2022
DOI: 10.3389/fmicb.2022.849585
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Function Insight of the α-Glucosidase QsGH13 From Qipengyuania seohaensis sp. SW-135

Abstract: The α-glucosidases play indispensable roles in the metabolic mechanism of organism, prevention, and treatment of the disease, and sugar hydrolysis, and are widely used in chemical synthesis, clinical diagnosis, and other fields. However, improving their catalytic efficiency and production to meet commercial demand remains a huge challenge. Here we detected a novel GH13 family α-glucosidase, QsGH13, from the deep-sea bacterium Qipengyuania seohaensis sp. SW-135. QsGH13 is highly substrate specific and only hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Alpha-glucosidases and pancreatic alpha-amylases are the enzymes involved in the digestion of dietary carbohydrates and hence, are major determinants of postprandial blood glucose levels [10]. These enzymes act on polysaccharides at α−1,4-glycosidic bonds, breaking which liberates α-D-glucose [79,80]. Hence, inhibition of alpha-glucosidases and pancreatic alpha-amylases has established a role in the management of blood glucose in hyperglycemia associated with non-insulin-dependent diabetes mellitus [80].…”
Section: Discussionmentioning
confidence: 99%
“…Alpha-glucosidases and pancreatic alpha-amylases are the enzymes involved in the digestion of dietary carbohydrates and hence, are major determinants of postprandial blood glucose levels [10]. These enzymes act on polysaccharides at α−1,4-glycosidic bonds, breaking which liberates α-D-glucose [79,80]. Hence, inhibition of alpha-glucosidases and pancreatic alpha-amylases has established a role in the management of blood glucose in hyperglycemia associated with non-insulin-dependent diabetes mellitus [80].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, QsGH97a showed greater resistance to high concentrations of salt, detergents, and organic solvents in the presence of metal ions Ba 2+ or Sr 2+ . A novel esterase and an α-Glucosidase were also characterized in Qipengyuania seohaensis SW-135, which are highly alkaliphilic, halotolerant, and resistant to detergents and organic solvents 29 , 30 . The research has confirmed that this bacterium was a mildly halophilic bacterium and did not grow in a medium without NaCl or with addition of > 9% NaCl 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Protein samples were desalted and concentrated by a series of dilution/concentration steps, using 50 kDa Amicon Ultra centrifugal filter units (Millipore), until the concentration of imidazole reached below 1 μM. The protein was separated by 12.5% SDS-PAGE gel electrophoresis, and the concentration was measured by the method of Bradford with bovine serum albumin (BSA) as a standard ( Zhai et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…Kinetic parameters were determined using the respective optimal assay conditions using varying concentrations of selected substrates (0.001 to 1 mM). The values of K m and V max were obtained using the Michaelis–Menten equation, with GraphPad Software (GraphPad prism5, United States) ( Zhai et al, 2022 ). Averages of kinetic constants were determined for each enzyme based on three biologically independent experiments.…”
Section: Methodsmentioning
confidence: 99%